The Dimensions of Educational Evaluation (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2016)
By analysing the functions of educational evaluation we aimed to arrive at defining the dimensions of educational evaluation that offer insight into the process, resources, methods of evaluation from different perspectives – the dimensions. In this context, I defined three dimensions of educational evaluation: the personality dimension, where the levels of relationships between the object and the subject of educational evaluation are examined, the didactic dimension, the aim of which is to optimize the process of teaching and learning through the function of feedback, and the social dimension, the point of which is to enrich evaluation with the achievements of modern science, technology and social relations.